TECHNOLOGY OF NETWORK PARTNERSHIP ORGANIZATION WITHIN THE INTERACTION «SCHOOL - UNIVERSITY» - Dmitriy L. Schyogolev; Nina M. Kosova; Svetlana Yu. Likhacheva; Lyudmila V. Pavlova (Moscow Polytechnic University, 2016)
The article examines interaction between schools and universities by establishing "university education clusters". Professional orientation network center based on Nizhny Novgorod state university of architecture and civil engineering served as an example of educational institutions integration in the region. The project aims not only at developing future enrollees' positive motivation for professional self!determination, strong interest in sustainable engineering and construction trades, but also at improving school education in the region. Together with representatives of school administrations, the leading NNGASU professors have developed the principles of continuing interaction «School - university». The authors substantiate the necessity of expanding the network for including the leading enterprises of the Volga Federal District in the interaction.